Experimental Investigation on Green Synthesis of FeNPs using Azadirachta indica Leaves - Rathore, A.; Devra, V. (Journal of Scientific Research, 2022)
In nanotechnology, developing an environmentally friendly method for synthesizing iron nanoparticles (FeNPs) is an important aspect. According to recent studies, the use of secondary metabolites from plant leaf extract has recently emerged as a novel technology for synthesizing various nanoparticles. The leaf extract of Azadirachta indica was used to synthesize iron nanoparticles in this research. The effects of reactant concentrations, reaction temperature, and pH of the solution on the synthesis process of iron nanoparticles were studied. A UV-Visible Spectrophotometer that analyzed absorbance spectra was used to monitor the formation of iron nanoparticles in dispersion. Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) characterized the morphology of iron nanoparticles, and results reveal the particles are spherical with an average size of 48 nm. The optimum conditions for synthesis are as follows: 15 % leaf extract, [FeCl3] = 1.0 mM, pH 6.0, and temperature 60 °C. The FTIR technique confirms that plant biomolecules induce the reduction of Fe3+ ions to FeNPs and act as a capping and stabilizing agent. Therefore, they have good stability for various applications.